Upping the Anti: A Journal of Theory and Action - Biddle Erika; Conway Aidan; Fritsch Kelly (Toronto UTA Publications, 2009)
"Capitalism will inevitably find itself face to face with a starving multitude of enemployed workers demanding food or destruction of the social order that has starved them and robbed them of their jobs. In such a crisis the capitalism class cannot save itself...Its police and armies will be powerless to put down the last revolt. " Helen Keller
Keywords: 32